A ROADMAP TO PROFICIENT WRITING AND SPEAKING IN EFL CLASSROOMS - Maftuna Abdurasulova (Ta’lim innovatsiyasi va integratsiyasi, 2024)
This article explores strategies and techniques for fostering proficiency in writing and speaking within English as a Foreign Language (EFL) classrooms. It examines the importance of developing these skills for effective communication and academic success. Various methodologies and approaches are discussed, along with practical suggestions for implementation. The article concludes with recommendations for enhancing EFL students’ writing and speaking abilities, ultimately equipping them with the necessary tools for professional communication.